Quantitative structural mechanobiology of platelet-driven blood clot contraction. Issue 1 (December 2017) - Kim, Oleg; Litvinov, Rustem; Alber, Mark; Weisel, John
Abstract Blood clot contraction plays an important role in prevention of bleeding and in thrombotic disorders. Here, we unveil and quantify the structural mechanisms of clot contraction at the level of single platelets. A key elementary step of contraction is sequential extension–retraction of platelet filopodia attached to fibrin fibers. In contrast to other cell–matrix systems in which cells migrate along fibers, the "hand-over-hand" longitudinal pulling causes shortening and bending of platelet-attached fibers, resulting in formation of fiber kinks. When attached to multiple fibers, platelets densify the fibrin network by pulling on fibers transversely to their longitudinal axes. Single platelets and aggregates use actomyosin contractile machinery and integrin-mediated adhesion to remodel the extracellular matrix, inducing compaction of fibrin into bundled agglomerates tightly associated with activated platelets. The revealed platelet-driven mechanisms of blood clot contraction demonstrate an important new biological application of cell motility principles. Blood clot contraction is a cellular (patho)physiological process essential for wound healing, hemostasis, and thrombosis. Here, the authors describe the physical structural mechanism by which platelet filopodia pull "hand-over-hand" on fibrin fibers to compact them into bundled agglomerates.